PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. THE UNIVENUS SERANG - Nazhar Amin Firmansyah; Vera Maria (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine the effect of Leadership (X1), Organizational Culture (X2) and Work Motivation (X3) on Employee Performance (Y) at PT. The UnivenusSerang. The sampling technique in this study is simple random sampling, the sample in this study amounted to 68 respondents. The method of collecting data is using a questionnaire and the measuring instrument used is thescale Likert. By using software IBM SPSS Statistics 25. The results of the partial study (t test) state that the leadership variable has a tcount>ttablethat is 2,991 > 1,998 and a significance level of 0.004 < 0,05 meaning leadership has a positive and significant influence on employee performance, organizational culture variable has a t valuecount>ttablethat is 2,367 > 1,998 and a significance level of 0,021 < 0,05 means that organizational culture has a positive and significant influence on employee performance, and the work motivation variable has a value of tcount>ttablethat is 2,525 > 1,998 and the level of significance of 0,014 < 0,05 means that work motivation has a positive and significant influence on employee performance.